A proposed conceptual model for orphan drug market entry - Nataša Jalen; Tina Vukasović (Mednarodno Inovativno Poslovanje)
The right to health is closely linked to the physical in mental well-being of all individuals in is a necessary condition for the realization of additional human rights, including the realization of an adequate standard of living. Rare diseases are diseases that affect a very small proportion of the population in have a special place because of their rarity. They are often chronic, progressive, life-threatening health conditions. Some of them can be treated with medicines called orphan drugs. Orphan drugs are developed by the pharmaceutical industry not for economic reasons, but to meet public health needs. New treatments need to be evaluated before they reach the market. This is done using health technology assessment, which assesses the relative effectiveness of new medicines, medical devices in other health technologies. The market entry of orphan drugs requires the active involvement of all stakeholders: marketing authorisation holders, competent authorities, the medical profession in patient organisations. Model of market entry for orphan drugs was developed using the qualitative methodology of constructivist grounded theory, tailored to the niche market in considers all key categories.